Effects of employing external condensers or phase-change materials on the performance of different solar still systems with different modifications - Shaaban M. Shaaban; Ali Basem; Suha A. Mohammed; Wissam H. Alawee; Hasan Sh Majdi; A. Aldabesh; Z.M. Omara; M.M. Younes (Case Studies in Thermal Engineering)
The yield of the solar still has been increased using a variety of techniques. The condensing surface's temperature has consequently risen, this negatively impacts the speed of condensing. Numerous techniques have been investigated to cool the condensing surface, such as water cooling, air cooling, adding phase-changing material (PCM), or an external condenser with a suction fan. Analysing previous investigations on cooling glass covers using an external condenser or PCM to ascertain which is more effective was the primary objective of this study. Also, this review aims to promote greater innovation in this field by highlighting promising directions for further investigation. The findings of the literature review indicate that cooling glass with a fan and condensing vapor in the feed water tank works better than cooling glass utilizing Nano PCM. Besides, the thermal efficiency ranges resulting from the addition of an external condenser or PCM are 42 %–72.4 % and 50.7 %–65 %, respectively. And the increases in solar still production when PCM or an external condenser is added range from 26 % to 44 % and 25 %–68 %, respectively. Where the lowest expenses per liter of freshwater generated by external condenser or PCM systems are 0.01 $ and 0.011 $, respectively. Consequently, as compared to PCM systems, solar still systems with an external condenser have higher output, better efficiency, and a lower cost per liter of freshwater.